Virtuous cycles and research for a regenerative urban ecology: The case of urban wood systems in Baltimore - Grove, Morgan; Carroll, Jeff; Galvin, Michael; Hines, Sarah; Marshall, Lauren L.; Wilson, Gene (Frontiers in Sustainable Cities, 2022)
The field of urban ecology has progressed since the mid-1990s through four major phases: an ecology in, of, for, and with cities. This progression reflects an interest to address the complexity of urban systems with social-ecological approaches. Further, this progression signifies an interest to address societal issues by co-designing and co-producing research in collaboration with diverse stakeholders from government, non-governmental organizations (NGOs), businesses, and community associations. What remains unaddressed in this progression is a research mission orientation. While there may be a range of goals for an ecology with cities, a focus on regenerative urban ecologies is crucial. Regenerative ecologies may be seen as an endpoint along a continuum from degenerative ecologies to sustainability to regenerative ecologies. Regenerative ecologies rely upon feedback loops, similar to coral reefs and climax forests. In urban systems, these feedbacks in social-ecological systems may be considered virtuous cycles that create reinforcing, positive benefits for people and nature over time. Virtuous cycles or feedbacks are often conceived as a singular, positive feedback loop. However, virtuous cycles may be most impactful, adaptive, and resilient when they contain multiple positive and negative feedbacks and synergies. Research has several important roles in advancing virtuous cycles and regenerative urban ecologies. In this paper, we use our urban wood systems project in Baltimore as both a case study and model to illustrate an approach and lessons learned for regenerative ecologies, virtuous cycles, and the role of research. We conclude with lessons learned and consider opportunities and constraints for virtuous cycles, research, and regenerative urban ecologies in Baltimore and to other urban systems.